Wideband Fan-Beam Lens Antenna for IR-UWB Through-the-Wall Human Detection Radar - Lee, Soyeong; Yoon, Daeyeong; Hwang, Kyuhwan; Wang, Heesu; Park, Kyung Hwan; Park, Yong Bae (IEEE Sensors Journal, 2025)
This article presents a fan-beam lens antenna design for impulse radio ultrawideband (IR-UWB) through-the-wall human detection radar applications operating in the 1-8 GHz. The proposed fan-beam lens antenna integrates a dielectric lens, designed by adjusting the lengths of dielectric slabs and air layers, with a Vivaldi antenna to achieve a fan-beam pattern characterized by a narrow beamwidth in the E-plane while maintaining a wide beamwidth in the H-plane. The antenna demonstrates excellent time-domain characteristics with a high fidelity factor exceeding 0.93, low reflection signal ringing, and maintained narrow beamwidth in the E-plane for far-field pulse radiation patterns. Through experimental validation, the antenna achieved SNR improvement due to concentrated signal propagation, enabling stable human detection at distances beyond 5 m through walls. The wide H-plane beamwidth allows effective detection of subjects in various postures, including lying positions. The proposed antenna design shows promising potential for various applications including disaster site search and rescue, building surveillance, fall detection in care facilities, noncontact vital sign monitoring, and smart home occupancy detection systems.
Keywords: Beam antennas; Beam widths; Dielectric lens; Fan beam antenna; Fan-beams; Human detection; IR-UWB radar; Tapered slot antennas; Through-the-wall radars; UWB radars; Dielectric lens; fan beam antenna; impulse radio ultrawideband (IR-UWB) radar; tapered slot antenna; through-the-wall radar